Faktor-Faktor yang Mempengaruhi Penyuluh dalam Pemanfaatan Media - E. O. M. Anwas; Sumardjo .; P. S. Asngari; P. Tjitropranoto (Jurnal Komunikasi Pembangunan, 2009)
A long side the community changes and demands, the competency of agricultural extension agents should beincreased by means of learning process. This learning process is not merely taken place within formal education butalso by means of the utilization of a variety of media whether they are mass media, programmed media, orenvironmental media. The present study was to analyze the media utilization intensity, and the dominant factorsinfluence their media utilization intensity. The study used explanatory research method on 170 agricultural extensionagents who work within paddy farmer area (Karawang) and within vegetable farmer area (Garut). Samples frompaddy farmer area were taken by using random sampling technique, while those from vegetable farmer area weretaken by using census method. Then data verification was conducted toward 206 farmers who were the clients of theagricultural extension agents. Data collection was conducted during February to April 2009. Data were analyzedusing descriptive technique and regression analysis. The result of the study showed that the extent of mediautilization tended to be at a low level. Several dominant factors influenced their media utilization.